2021
DOI: 10.1039/d1ta03513d
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of 1T-phase MoS2 nanosheets with abundant sulfur-vacancies through (CH3)4N+ cation-intercalation for the hydrogen evolution reaction

Abstract: 1T-phase molybdenum disulphide (MoS2) is considered as one of the most promising candidates to substitute noble metals in hydrogen evolution reaction (HER). Fabricating single layer 1T-phase MoS2 with abundance sulfur...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Although 1T‐MoS 2 is better than 2H‐MoS 2 in our study, its alkaline HER performance is inferior to that reported in literature. For example, Jin et.al reported (CH 3 ) 4 N + ‐intercalated single‐layer 1T‐MoS 2 requires an overpotential of 176 mV to achieve a current density of 10 mA cm −2 , [ 14 ] and Anjum et.al reported that NH 3 ‐intercalated 1T/2H MoS 2 requires 229 mV. [ 66 ] Interestingly, 2H‐MoS 2 with moiré structure is reported to have an improved HER performance in acidic media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 1T‐MoS 2 is better than 2H‐MoS 2 in our study, its alkaline HER performance is inferior to that reported in literature. For example, Jin et.al reported (CH 3 ) 4 N + ‐intercalated single‐layer 1T‐MoS 2 requires an overpotential of 176 mV to achieve a current density of 10 mA cm −2 , [ 14 ] and Anjum et.al reported that NH 3 ‐intercalated 1T/2H MoS 2 requires 229 mV. [ 66 ] Interestingly, 2H‐MoS 2 with moiré structure is reported to have an improved HER performance in acidic media.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Much improvement has been achieved on half-reaction performance by developing HER or OER catalysts, including both noble-metal based catalysts, [2,10,11] and noble-metal-free catalysts. [12][13][14][15] On the other hand, developing a single electrocatalyst coupling both HER and OER activities in the same electrolyte for overall water splitting is more attractive for practical applications, and is therefore technologically important yet challenging. [9,16,17] To date, the main route for industrial HER/OER is the electrolysis of water in alkaline solution due to its mild condition, where higher stability of the electrode material can be retained.…”
Section: Doi: 101002/smll202107238mentioning
confidence: 99%
“…However, the existence of MoS 2 can be confirmed in the HR‐TEM image of 3 % MoS 2 /ZnIn 2 S 4 photocatalyst. As illustrated in Figure 2j, the lattice fringes of (002) plane with d‐spacing distance of 0.61 nm and (102) planes with a d‐spacing distance of 0.32 nm were assigned to MoS 2 and ZnIn 2 S 4 , respectively [26,27] . Figure 2k and 2 l shows the elemental mapping of 3 % MoS 2 /ZnIn 2 S 4 photocatalyst, in which the Zn, In, Mo and S elements have the homogeneous distribution, confirming the relatively uniform growth of MoS 2 on ZnIn 2 S 4 .…”
Section: Resultsmentioning
confidence: 68%
“…As shown in figure 1(a), CdS NWs with abundance S-vacancy can be easily prepared through the hydrothermal route in ethylenediamine with cadmium nitrate and thiourea as precursors according to our previous work [39]. Electron spin resonance (ESR) spectroscopy (figure 1(b)) indicates the abundant S vacancies in CdS NWs as a peak at ∼351 mT with significantly higher intensity is observed [40].…”
Section: Resultsmentioning
confidence: 99%